2019
DOI: 10.1016/j.socscimed.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

'There is no point giving cash to women who don't spend it the way they are told to spend it' – Exploring women's agency over cash in a combined participatory women's groups and cash transfer programme to improve low birthweight in rural Nepal

Abstract: Cash transfer programmes form an integral part of nutrition, health, and social protection policies worldwide, but the mechanisms through which they achieve their health and nutritional impacts are incompletely understood. We present results from a process evaluation of a combined participatory women's groups and cash transfer programme to improve low birth weight in rural Nepal. We explored the ways in which context, implementation, and mechanism of the intervention affected beneficiary women's agency over ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…These findings reflect the exact presumptions that drive the use of CM in marginalized communities, where it is assumed that women hold less power than others, impacting their ability to take care of their health needs [1]. Manifestations of gender inequity such as these have been reflected in other studies using CM [17], illustrating how women's low social status influences everything from community priority setting, to household decision making, to the participation of women in CM interventions not directly targeted toward them [18]. Addressing complex problems, such as maternal mortality, requires multifaceted solutions such as CM coupled with MWHs and health facility strengthening, yet reporting and evaluation is a continued challenge.…”
Section: Discussionsupporting
confidence: 54%
“…These findings reflect the exact presumptions that drive the use of CM in marginalized communities, where it is assumed that women hold less power than others, impacting their ability to take care of their health needs [1]. Manifestations of gender inequity such as these have been reflected in other studies using CM [17], illustrating how women's low social status influences everything from community priority setting, to household decision making, to the participation of women in CM interventions not directly targeted toward them [18]. Addressing complex problems, such as maternal mortality, requires multifaceted solutions such as CM coupled with MWHs and health facility strengthening, yet reporting and evaluation is a continued challenge.…”
Section: Discussionsupporting
confidence: 54%
“…Acknowledging the constraints that unequal gender power dynamics have on women's lives, there is growing interest in promoting gender equality and women's and girls' empowerment (WGE) as a means to accelerate development and improve women's health and well-being ( Kavanaugh and Anderson, 2013 ; Sonfield et al, 2013 ). A woman's ability to make strategic SRH decisions and act on those choices relates to her well-being, as evidenced by studies linking women's empowerment to improved SRH behaviors and outcomes ( Prata et al, 2017 ), including use of contraception ( Bose and Heymann, 2019 ; Ewerling et al, 2017 ; James-Hawkins et al, 2016 ; Yaya et al, 2018 ), prevention of unintended pregnancy ( Upadhyay and Hindin, 2005 ), receipt of antenatal care ( Mistry et al, 2009 ), improved maternal dietary practices ( Gram et al, 2019 ), delivery with a skilled birth attendant ( Shimamoto and Gipson, 2015 ), and negotiation in sexual relationships ( Pearson, 2006 ; Wolff et al, 2000 ). However, a recent review on empowerment and family planning by Prata and colleagues reported inconsistent results regarding the contribution of empowerment to women's current use of family planning, which likely reflects differences in the conceptualization of empowerment across studies, outcomes examined in analyses, and normative views about family planning behaviors across populations ( Prata et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…These inequalities may increase during seasons of shortage, especially for micronutrient-rich foods groups (29) and during periods of peak agricultural activity (30) . The low status of young reproductive age women in our setting (76)(77)(78) may magnify the impact of seasonal stresses, since 'junior' daughters-in-law usually cook and eat last, feeding micronutrient-rich foods to others while leaving little or none for themselves (79) .…”
Section: Discussionmentioning
confidence: 99%